Pra Rancangan Pabrik Asetanilida dari Anilin dan Asam Asetat Kapasitas 25.000 Ton/Tahun - Miko, Biro Dina, Muhammad Mujiburohman, S.T., M.T., Ph.D, Emi Erawati, S.T., M.Eng (2016)
Acetanilide an acetyl derivative of aromatic amines that are classified as primary amide. Acetanilide needs from year to year continues to increase so that the need for increased production with the establishment of the factory acetanilide. For that we need acetanilide plant design. Acetanilide mill is designed with a capacity of 25,000 tons / year which is expected to meet the domestic needs and even export Acetanilide making process is carried out by liquid phase acylation reaction amide mole ratio of aniline: acetic acid = 1: 2. The reaction is exothermic and the reactor is run in Continuous Stirred Tank Reactor (CSTR), liquid-liquid phase, reversible and kept isothermal operating conditions (120oC) and a pressure of 1 atm. Acetic acid requirement for this plant as much 4.734,8485 kg/hour and needs as much aniline 6.106,9986 kg/hour. Products such as acetanilide 3.297,7828 kg/hour. Utilities include water provision process support for 25.698,4146 kg/h obtained from Bengawan Solo river water, the supply of saturated steam at 1.563,8558 kg/h obtained from the boiler with fuel oil amounted to 136,3039 liters of fuel per hour, the air needs press amounted to 56,0736 m3/hour, the electricity needs of 292,8875 kW obtained from PLN and generator sets. The factory was founded in Kebak Kramat, Karanganyar, Central Java with a land area of 20,000 m2 and the number of employees 208 peoples. Acetanilide mill uses fixed capital of Rp 370.758.439.187,55 and working capital of Rp 214.417.969.984,39. From the economic analysis of this plant show a profit before tax of Rp 202.320.430.263,76 per year and after tax of Rp 161.856.344.211,00 per year. Percent Return On Investment (ROI) before taxes 55% and 44% after tax. Pay Out Time (POT) before tax for the year of 1.55 and 1.86 after tax during the year. Break Even Point (BEP) by 40%, and Shut Down Point (SDP) by 26%. Discounted Cash Flow (DCF) accounted for 43%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set. Keywords: acetanilide, aniline, acetic acid, factory design